Perception of 'Legal Consideration in Educational' in Elementary School: A Review of Literature - Elihami, Elihami (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Legal considerations are integral to shaping educational practices in elementary schools, ensuring compliance with federal and state laws and upholding the rights of students. This literature review investigates perceptions of legal aspects in elementary education, focusing on anti-discrimination laws, special education mandates, student privacy, safety regulations, employment laws, curriculum standards, disciplinary protocols, technology integration, and parental engagement. Schools must adhere to laws prohibiting discrimination based on race, color, sex, disability, and religion, ensuring equitable access to educational opportunities. The Individuals with Disabilities Education Act (IDEA) mandates provision of suitable services, including Individualized Education Programs (IEPs), to students with disabilities, guaranteeing them a free and appropriate education. Compliance with the Family Educational Rights and Privacy Act (FERPA) is essential to safeguard student records' privacy. Moreover, schools must maintain safe learning environments, comply with employment laws, and ensure curricula cater to diverse learning needs. Establishing fair disciplinary measures, respecting due process rights, and acknowledging teachers' and administrators' legal responsibilities are critical. Additionally, navigating legal aspects of technology use and fostering parental involvement are imperative for ensuring compliance and enhancing student well-being and success.